Polis democracy of the European antiquity in accounts of ancient and modern authors - Khankevich, Olga I. (Journal of the Belarusian State University. Law, 2019)
The article examines the political and social system of the Greek classical polis (V–IV centuries BC) and the Roman republican civitas (V–I centuries BC), which are called the civil community in antiquity studies of modern era. Polis and civitas reproduced a three-part model of governance, which was usual for the primary society, in the form of a council of elders, a people’s congress and officials, or magistrates, which were bearers of military and civil authority. The democratic traditions of the polis and civitas were embodied in the principles of election, collegiality and regular replacement of all branches of power, as well as in the ways of adopting laws and forms of protection of the rights and interests of full members of the polis community – citizens (Greek πολίτης, Latin civis). The study of the problem stated in the title of this article is based on the active use of evidence of historical and legal sources of antiquity, as well as modern accounts of the political democracy of European antiquity. The general conclusion of the author is the proposition that the Greek classical polis and the Roman republican civitas bequeathed to humanity three great ideas – citizenship, republicanism and democracy. The world-wide significance of these ideas lies in the fact that the ancient Greeks and Romans were able to realize them into practice.
Keywords: polis; civitas; republic; democracy; citizen; civil law